Trends in the Development of Legal Regulation of International Commercial Activity in the Context of Digital Transformation of the Business Environment - Olga V. Sergeeva (LAW AND BUSINESS, 2026)
The article is devoted to the trends in the development of legal regulation of international commercial activity in the context of digital transformation of the business environment. The international standards developed in this area by the International Chamber of Commerce and the United Nations Commission on International Trade Law (UNCITRAL) are analyzed. It is concluded that, in one form or another, the idea of developing a unified standard for international commercial transactions using electronic, digital and intelligent technologies is increasingly being heard and expressed in specific initiatives. In this respect, the participation of States in the legal provision of conditions for the effective functioning of the global trading system, the adaptation of business entities to changing market conditions, and the integration of new technological solutions into commercial circulation is of particular importance.